The influence of work morale, work discipline, and work environment on employee performance - Suwandi; Tendy Setiawan (Privietlab, 2022)
This study aims to determine the effect of work morale, work discipline, and work environment on employee performance. This research method is quantitative. The source of data in this study is primary data. The primary data used is by distributing questionnaires to the respondents consisting of questions for which answer choices have been provided using a Likert scale. Likert scale with a scale range of 1-5. The population used in this study were employees of PT SAI, the sampling technique used in this study was a saturated sampling technique with a population of 44 respondents. The analytical technique used in this research is multiple regression test with the help of SPSS 25.0 program. The results showed that work morale, discipline and work environment had a positive and significant effect on employee performance.